Способи зниження зварювальних залишкових напружень і деформацій - Жильцов, А. В.; Васюк, В. В. (Енергетика і автоматика, 2017)
WAYS OF DECREASE WELDING RESIDUAL STRESSES AND STRAINS А. Zhiltsov, V. Vasuk During welding the metal structure it may have residual stress and strain result in the distortion of design shapes and sizes of products that require recovery improper external coercion. When using residual stresses and plastic deformation of the metal can cause fatigue and brittle fracture, changing stiffness, reduce corrosion resistance and precision welded construction. By the time the existence of stress and strain are divided into temporary and residual. In case stress values not to exceed the elastic limit of the metal, after cooling body these tensions disappear. Residual stresses cooling body is completely removed, since they involve irreversible plastic deformation and local structural changes in the structure of the material when the magnitude of the stress they exceed the limit of turnover of construction materials, mechanism of reduction is relaxation. The study is research existing ways to reduce welding residual stresses, determine their strengths and weaknesses. Material and methods of research. Ways to prevent the emergence of stresses and strains in welding include: rational design of welded assemblies, rational choice method and welding technology, implementation of the relevant requirements in sladanni designs, reasonable choice of welding technology. By ways to reduce residual welding stresses include: heat treatment, machining vibration, ultrasound, shock and explosive loading, rolling, forging, etc. An apparatus for making such a pulsed electromagnetic effects might constructively be done in the form of electrode systems and induction-type pulse generator power. The principle of operation of which is the accumulation of electrical charge in the capacitor is happening when powered by a regulated DC voltage by great resistance and subsequent rapid discharge of the capacitor through the inductor and the electrode system. Among a number of existing ways to reduce welding residual stresses electrodynamic treatment has significant benefits and requires further research towards the development of mathematical models of unsteady electrophysical process electrodynamic treatment of welded joints and installation on the basis of structural, electrical and operational characteristics for the parameters of current pulses sufficient for effective regulation residual stress state in metal structures.